ACTIONS SPEAK LOUDER THAN WORDS: IMPACT OF KINESICS ON UNDERGRADUATE MEDICAL EDUCATION - Aziz, Anbreen; Khan, Asma Munir; Niazi, Zainab; Mirza, Tayyeba Iftikhar; Fazal, Sabeen (Journal of Ayub Medical College Abbottabad, 2021)
Background: Nonverbal communication constitutes significant proportion of human communication besides spoken words. This study explored teacher's perceptions about impact of kinesics (facial expressions, gestures, head movements and postures) on undergraduate medical education within a classroom setting. Methods: A survey-based exploratory research was carried out from July-August 2020. Medical teachers from two private dental colleges of Islamabad were included in the sampling frame. The survey questions were validated and approved by all authors before execution. Frequencies and percentages of closed-ended questions were calculated while thematic analysis for open-ended questions was done by all authors to get consensus on themes, hence ensuring analytical triangulation. Results: Forty-six teachers responded to the survey. The most frequently shown facial expressions were '˜happiness and enthusiasm' (76.1%) creating friendly, conducive, and motivating learning environment. '˜Smile' was considered powerful communicative signal (95.7%) whereas '˜anger' was thought to be communication barrier leading to stressful and demotivating learning environment. Neutral expressions were considered helpful to maintain class decorum. '˜OK sign with raised thumb' (50%) was found helpful to develop special teacher-student connection and '˜head nod' (84.8%) was encouraging students to continue giving answers. Standing posture (81%) exhibited teacher's commitment towards teaching and produced active learning environment. Conclusion: Teachers should start lecture with welcoming facial expressions, i.e., smile to build rapport with students. Anger should be avoided as it demotivates students by making learning environment stressful. We need to train faculty regarding effective use of nonverbal communication strategies to improve student's learning experience and to create positive learning environment.